Analisis Kaplan Meier terhadap Perbaikan Klinis Batuk pada Pasien Pneumonia Anak yang Diberikan Terapi Tambahan Vitamin D - Arief Rafsanjani; Endang Darmawan; Nurcholid Umam Kurniawan; Tri Puspita Yuliana; Aditya Noviadi Rakhmatullah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Pneumonia is the leading cause of death in children under five years of age and contributed to 14% of total global child deaths in 2013. Pneumonia is an inflammation of the lungs caused by bacteria, viruses, fungi, parasites and attacks the lung parenchyma. After receiving antibiotic therapy, the cure rate for pneumonia is relatively high, but the mortality rate due to pneumonia infection is still high. Therefore there needs to be an effort to add therapy to improve patient clinical outcomes. Vitamin D plays a role in the body's defense function, both in natural and adaptive immunity and in the body's defense in cases of infection, malignancy, and autoimmunity. This study was an experimental double-blind, randomized clinical trial that was analyzed using Kaplan Meier. The research subjects were children aged six months to 18 years divided into two treatment groups, namely the treatment group (n = 35) and the control group (n = 35). The treatment group received vitamin D, while the control group a placebo. The data taken included the results of clinical studies of patients. This study indicates that vitamin D is effective in accelerating the cough frequency of patients infected with pneumonia.